The Effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) on Stock Price in Telecommunications Sub-Sector Companies Registered at Indonesia Stock Exchange with 2014-2021 Period - Cahyani Leo Nita Sowandi; Pujiarti Pujiarti (Komunitas Dosen Indonesia, 2023)
Investors will consider which companies to choose. The technology sector is one option for investors to invest their capital. Stock prices affect investors who will invest their capital. The supply and demand for the shares of the company in question affect the price of these shares, which varies. To determine whether the independent, namely the current ratio (X1), debt to equity ratio (X2), and earnings per share (X3), have an impact on stock prices as the dependent variable in Telecommunication Subsector Companies Registered in IDX Period 2014–2021, this research was carried out. In this study, there were 9 companies in the population, and 4 companies were chosen for the sample using a purposive sampling technique. According to the findings from the tests, there is an effect between the current ratio and stock prices, but there is no effect between the debt-to-equity ratio and stock prices and no effect between the earning per share and stock prices. Based on the test results simultaneously there is an influence between the Current Ratio, Debt to Equity Ratio, and Earning Per Share on Stock Prices